Cancer patients and targeted therapy during COVID‐19 pandemic: A descriptive case series study - Kasra Khodadadi; Minoosh Moghimi; Reza Mansouri (Clinical Case Reports, 2022)
Abstract To evaluate the effectiveness of targeted therapy on preventing or treating COVID‐19, in this study, we want to share our experience about 14 patients (nine women, five men; average age, 59 years) who were treated with targeted therapy due to their underlying malignant disorders in our center.